PENGARUH GROWTH OPPORTUNITY, KEPEMILIKAN MANAJERIAL DAN KEPEMILIKAN INSTITUSIONAL TERHADAP NILAI PERUSAHAAN SEKTOR KESEHATAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019-2022 - Rachman, Muhammad Aditya; Harnida, Muthia; Santi, Apriya (Jurnal Ilmiah Ekonomi Bisnis, 2024)
The purpose of this study is to identify and analyze growth opportunity, managerial ownership and institutional ownership of the value of health sector companies listed on the Indonesian Stock Exchange (IDX) for the 2019–2022 period. The research method uses a quantitative approach with explanatory research method. The data used in this study is secondary data, namely company reports from the 2019-2022 period in the health sector. The population of this study are health sector companies listed on the IDX in the 2019-2022 period, totaling 68 companies. With a purposive sampling technique, a sample of 17 companies was obtained. The analysis technique in this study used multiple regression analysis, t test, F test and determination test through the SPSS program. The results of the study show that growth opportunity has an effect on the company value of companies listed in the health sector which are listed on the IDX in 2019-2022. Managerial ownership has no effect on the company value of companies listed in the health sector listed on the IDX in 2019-2022. Institutional ownership has no effect on the company value of companies listed in the health sector listed on the IDX in 2019-2022. Keywords: Growth Opportunity, Managerial Ownership, Institutional Ownership, Firm Value